Physical exercise for primary sarcopenia: an expert opinion - Antimo Moretti; Federica Tomaino; Marco Paoletta; Sara Liguori; Sara Liguori; Silvia Migliaccio; Mariangela Rondanelli; Angelo Di Iorio; Raffaello Pellegrino; Davide Donnarumma; Daniele Di Nunzio; Giuseppe Toro; et al. (Frontiers in Rehabilitation Sciences)
Sarcopenia is the age-related loss of skeletal muscle mass and function. Recently, research has focused on defining diagnostic criteria for this condition, now recognized as a muscle disease with a specific identifying code (ICD-10: M62.84). The diagnostic process for sarcopenia involves several stages, including the use of dedicated questionnaires and objective measurements of muscle strength and mass. According to international guidelines, therapeutic exercise is recommended to improve muscle mass, muscle strength, and physical performance. However, much of the supporting evidence comes from studies on non-sarcopenic elderly patients. Among types of therapeutic exercise, guidelines mainly emphasize muscle strengthening. The prescription of therapeutic exercise must consider the clinical and functional conditions of the patient (e.g., the presence of severe sarcopenia) and patient preferences. Muscle strengthening should target large muscle groups and include low-intensity resistance exercise for strength improvement, or high-intensity resistance exercise for additional benefits in muscle mass and function. Evidence suggests that an ideal therapeutic exercise program for sarcopenic patients should be multimodal, incorporating muscle strengthening, aerobic exercise, and balance control programs. This approach could enhance patient adherence by offering variety. Although multimodal therapeutic exercise improves muscle mass and function, these benefits can be lost during prolonged physical inactivity. Therefore, the exercise prescription must define intensity, volume (repetitions and sets), frequency, rest intervals, and duration, tailored to the type of exercise. Aerobic training programs improve endurance and optimize mitochondrial function. Balance training, important for reducing the risk of falls, should be done at least three times a week. Muscle strengthening should be done at least two days a week, starting at 50%–60% of 1 repetition maximum (RM) and progressing to 60%–80% of 1 RM, with approximately 10 exercises per session. Adopting comprehensive prescription protocols, such as those proposed in this paper, can significantly aid in the functional recovery and well-being of patients with sarcopenia.